Acinetobacter baumannii clinical isolates from outbreaks in Erbil hospitals after the COVID-19 pandemic - Hazheer M Hamad; Hanan T Subhi (Journal of Infection in Developing Countries)
Introduction: Acinetobacter baumannii is endemic in hospital environments, and since the coronavirus disease 2019 (COVID-19) pandemic, multidrug-resistant A. baumannii has become more potent. This potential evolution is driven by the undetectable numbers of gene resistances it has acquired. We evaluated the antibiotic-resistance genes in isolates from patients in Erbil hospitals.